Analysis Of Islam-Based Sex Education Content On Instagram @taulebih.id - Nurrahmah, Sahidah; Soiman, Soiman (UNIVERSITAS PAKUAN, 2023)
This research aims to know the content of Islamic sex education on the instagram account @taulebih.id. this research uses qualitative descriptive methods with the type of content analysis study (content analysis). Data sources in this study include primary data obtained directly through the research arena and secondary data acquired indirectly through literature relevant to the context of the research. Data collection techniques in this study include observation and documentation. The implementation of research data is carried out with techniques, data reduction, data presentation, and data verification. The results of this study show that Islamic sexual education content can be an effective means to convey information and education about sexuality in Islamic views. Islam-based sex education content can help people understand and appreciate Islamic values in terms of sexuality and help avoid inappropriate and sharia-violent sexual behavior. Some sex education content based on Islam can be presented on the Instagram account @taulebih.id among others: (1) Religious marriage, is it possible? (2) Abortion Law for Victims of Rape; (3) The Effect of Masturbation. Islam-based sex education content presented on the Instagram account is informative, and useful for Instagram users for positive reasons, educating, and in accordance with values in Islamic religion.